Optical Simulation Study of Perovskite/CIGS Tandem Solar Cells With Reduced Graphene Oxide Layers - Kovačič, Milan; Krč, Janez; Savva, Kyriaki; Maragkaki, Stella; Stratakis, Emmanuel; Rashid, Mudasar; Tutundzic, Merve; Kuang, Yinghuan; de Wild, Jessica; Aernouts, Tom; Vermang, Bart; Topič, Marko (Frontiers in Photonics, 2022)
Tandem solar cells present a promising solution to overcome the Schottky-Queisser efficiency limit of single-junction solar cells. In this paper an all-thin-film tandem solar cell based on perovskite (PK) top cell and chalcopyrite Cu(In, Ga)Se2 (CIGS) bottom cell is researched. Device optical simulations are validated on the top and bottom cell separately and employed to investigate optical effects of introduced laser-reduced graphene oxide (rGO) layers at two positions in the tandem cell, namely on top of PK cell underneath the front transparent electrode and at the position between the top PK and bottom CIGS cell. The purpose of introduced rGO layers is to improve optoelectrical properties of the device, based on tunable electronic and optical characteristics of rGO layers. Optical simulation results show that the parasitic absorption in rGO layers may noticeably affect the performance of the tandem cell if the layers are not optimized. The use of very thin (a few nm) rGO is suggested from the analysis if the parasitic absorption of layers is not reduced. Directions for further optimization of optical rGO, including reduction of parasitic absorption and tuning of the real part of refractive index is performed.